Seasonal Variability and Future Projection of Ocean Acidification on the East China Sea Shelf off the Changjiang Estuary - Guo, Xianghui; Yao, Zhentong; Gao, Ying; Luo, Yaohua; Xu, Yi; Zhai, Weidong (Frontiers in Marine Science, 2021)
Ocean acidification (OA) occurs universally in the world oceans. Marginal seas are facing more serious OA than the open ocean due to strong anthropogenic and natural impacts. This study investigates carbonate dynamics on the East China Sea (ECS) shelf off the Changjiang estuary using field observations made from 2015-2019 that cover all four seasons. In the low productivity cold seasons, the water was well mixed vertically. The coastal area and the northern ECS was occupied by water characterized by high DIC (dissolved inorganic carbon), low pH25 (pH at 25 oC) and low Ar (saturation state index of aragonite), and influenced by Yellow Sea Coastal Water. However, during highly productive warm seasons, pH25 and Ar increased in surface water but decreased in bottom water as the result of strong biological DIC uptake in the surface water and CO2 production by strong organic matter remineralization in the bottom water. Strong remineralization decreased pH25 and Ar by 0.180.08 and 0.730.35 in the hypoxic bottom water in summer. Even though the bottom water remained oversaturated with respect to aragonite (Ar >1.0) during the surveys. Under the context of global ocean acidification and the strong seasonal acidification, the projected bottom water on the ECS shelf will be corrosive for aragonite by mid-century.